Evidence of altered mucosa-associated and fecal microbiota composition in patients with Irritable Bowel Syndrome - Sundin, Johanna; Aziz, Imran; Nordlander, Sofia; Polster, Annikka; Hu, Yue O. O.; Hugerth, Luisa W.; Pennhag, Alexandra A. L.; Engstrand, Lars; Törnblom, Hans; Simrén, Magnus; Öhman, Lena (Scientific reports, 2020)
Altered bacterial composition and small intestinal bacterial overgrowth (SIBO) may be associated with irritable bowel syndrome (IBS). This study aimed to determine the fecal and mucosa-associated bacterial composition along the gastrointestinal (GI) tract and to assess SIBO in IBS. Bacterial composition of feces, and mucosa of the duodenum and sigmoid colon was determined by 16S rRNA-amplicon-sequencing. SIBO was evaluated by bacterial culture of duodenal aspirate, glucose and lactulose breath tests. Mucosal antibacterial gene expression was assessed by PCR Array. The bacterial profiles of feces and the mucosa of sigmoid colon, but not duodenum, differed between IBS patients (n = 17) and HS (n = 20). The IBS specific bacterial profiles were linked to the colonic antibacterial gene expression. Fecal bacterial profile differed between IBS subtypes, while the mucosa-associated bacterial profile was associated with IBS symptom severity and breath tests results at baseline (H 2 and/or CH 4 ≥ 15 ppm). The prevalence of SIBO was similar between IBS patients and HS. This study demonstrates that alterations in the bacterial composition of the sigmoid colon of IBS patients were linked to symptoms and immune activation. While breath tests reflected the mucosa-associated bacterial composition, there was no evidence for high prevalence of SIBO or small intestinal bacterial alterations in IBS.